The Connection Between Goals and Rewards in a Social Entrepreneurship - Supriyanto; Sasongko, Fusthatthul Nur (Danadyaksa: Post Modern Economy Journal, 2025)
Social Entrepreneurship is a growing business model that addresses social and environmental issues through products and services. In Indonesia, the ecosystem supporting Social Entrepreneurship is expanding, but the lack of a unified definition and slow government recognition has led to varied practices and outcomes. This study aims to explore how Social Enterprises disclose their corporate identity and maintain accountability. Using Identity and Stakeholder Theory, the study examines five key identity aspects: mission, activity, governance, performance, and accountability. A multiple case study approach was applied to 10 Indonesian Social Enterprises chosen for their prominence and diversity. Data were gathered from official company websites, supported by interviews and CEO presentations from webinars in 2022 and 2023. Thematic analysis using NVivo software identified patterns across these identity aspects. The findings show that Social Enterprises prioritize social values like community development, empowerment, welfare, and sustainability over profit generation. Institutional commitment is reflected in impact reports, achievement profiles, SDG disclosures, and media coverage. However, financial performance is rarely disclosed, and accountability practices vary between formal impact reporting and informal stakeholder engagement. This study contributes by offering a framework for understanding how Social Enterprises disclose their identity and stay accountable. It also provides practical guidelines for policymakers and practitioners to strengthen the Social Entrepreneurship ecosystem in Indonesia. Future research should further explore the financial performance and long-term impact of Social Enterprises to balance social and economic goals.